Pengaruh Financial Literacy, Financial Attitude, dan Hedonistic Lifestyle Terhadap Financial Management Behavior Pengguna PayLater - Permata, Rika Wahyu; Trisnaningsih, Sri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The rapid progression of financial technology during the Society 5.0 era has brought about transformative changes in personal finance management, exemplified by the emergence of innovative digital financial services like PayLater. This research explores the extent to which financial literacy, financial attitude, and a hedonistic lifestyle influence financial management behavior, with an emphasis on college students who utilize PayLater services. A quantitative method was implemented, applying purposive sampling to choose 130 students from the Accounting Department at UPN “Veteran” East Java. Data collection was conducted using an online survey designed to evaluate four key constructs: financial literacy, financial attitude, hedonistic lifestyle, and financial management behavior. The data were analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method, which facilitated the assessment of relationships among the studied variables. Findings reveal that all three independent variables financial literacy, financial attitude, and hedonistic lifestyle significantly impact the financial management behavior of students who use PayLater. These findings are consistent with the Theory of Planned Behavior, which emphasizes the role of cognitive and behavioral elements in shaping financial decision-making. Ultimately, the research contributes meaningful insights into how digital-age financial behaviors are shaped, particularly in the context of delayed payment mechanisms like PayLater.